Structured transition is associated with improved outcomes in diabetes. (1st February 2022) - Harmer, Matthew J; Everitt, Lucy H; Parker, Lillie; Davis, Nikki; Connett, Gary; Nagra, Arvind
Abstract: This study aimed to assess the effectiveness of a structured transition tool for the successful transitioning of young people (YP) with type 1 diabetes from paediatric to adult diabetic services. In a single‐centre retrospective observational study, case notes were reviewed for YP with type 1 diabetes transitioning between paediatric and adult services between 2011–2014. YP were split into those who had participated in the 'Ready Steady Go' (RSG) structured transition programme as part of their routine care, and those who had not (RSG versus non‐RSG). Between group comparisons were made for changes in objective measures before and after transfer to adult services including: glycated haemoglobin (HbA1c ), non‐high density lipoprotein (HDL) cholesterol concentrations and non‐elective diabetes‐related hospital admissions. Case note documentation of advice given during consultations was also reviewed. Data were available for 106 YP. Of these, 71 had participated in the RSG transition programme. Programme use was associated with lower non‐elective, diabetes‐related hospital admissions and lower non‐HDL cholesterol concentrations compared with historical controls. The rise in HbA1c typically observed in YP during early adult life did not occur in the intervention group. No differences were observed in total cholesterol concentrations and body mass index. Trends towards higher rates of documentation of key topic discussions in the RSG group were significant for contraception and pregnancy. Due to the observed improvements in markers of metabolic and diabetes control, this study supports the role of a structured transition tool such as the 'Ready Steady Go' programme for YP with type 1 diabetes. Copyright © 2022 John Wiley & Sons.